Efektivitas Pemungutan Pajak Hotel dan Kontribusinya Terhadap Pendapatan Asli Daerah Kabupaten Ngada : Studi Kasus Pada Unit Pelaksana Teknis Pendapatan, Pengelola Keuangan dan Aset Daerah Kabupaten Ngada - Lengu, Maria Goreti; Reo, Hermanus; Marselina, Apriana (Jurnal Riset Ilmu Akuntansi, 2021)
This study aims to determine the effectiveness of hotel tax revenues and hotel tax contributions to local revenue. This type of descriptive qualitative research.The results showed that the effectiveness of the hotel tax on the UPT Revenue, Financial Management and Regional Assets of Ngada Regency from 2014-2018 fluctuated with quite effective and effective categories. This can be seen in the level of effectiveness in 2014 of 85.27% with a fairly effective category. Meanwhile, in 2015 the effectiveness of hotel tax decreased by 80.00% with quite effective category. In 2016 the level of effectiveness increased to 85.41% in the quite effective category. In 2017 the effectiveness level also increased to 99.01% in the effective category and in 2018 the effectiveness level decreased to 93.43% in the effective category. The hotel tax contribution to the UPT of Regional Original Revenue, financial management and Regional Assets of Ngada Regency from 2014 to 2018 was still below 10% or very less contributed according to the contribution criteria table.